Club Cell Secretory Protein–Derived Acute Respiratory Distress Syndrome Phenotypes Predict 90-Day Mortality: A Reanalysis of the Fluids and Catheter Treatment Trial. (27th May 2022) - Chase, Aaron; Almuntashiri, Sultan; Sikora, Andrea; Zhang, Duo
Abstract : OBJECTIVES: Club cell secretory protein (CC16) is a protein with potential utility as a lung-specific biomarker for acute respiratory distress syndrome. The purpose of this study was to characterize CC16 in plasma from patients enrolled in the Fluid and Catheter Treatment Trial (FACTT) to determine the prognostic value for patient outcomes in our subgroup of FACTT patients. DESIGN: A secondary biomarker analysis of a prospective randomized-controlled trial. The primary outcome was area under the receiver operating characteristic (AUROC) of CC16 for prediction of 90-day mortality. Secondary outcomes included differences in mortality, length of stay, and ventilator-free days (VFDs) between patients with high and low CC16. Statistical analyses were performed with IBM SPSS Statistics. SETTING: Single-center laboratory analysis. SUBJECTS: Plasma samples from 68 FACTT subjects and 20 healthy controls. INTERVENTIONS: CC16 was measured in patient plasma samples by enzyme-linked immunosorbent assay. MEASUREMENTS AND MAIN RESULTS: Subjects were an average of 48 years old (sd, 16.7 yr old) and 51.5% male. AUROC analysis of CC16 on day 1 showed an area under the ROC curve of 0.78 for prediction of mortality (odds ratio, 1.011; 95% CI, 1.003–1.021) with an optimal cutoff value of 45 ng/mL. Patients in the low CC16 group (<45 ng/mL) had lower mortality (7.5 vs 50.0%; p < 0.001) and similar VFD (11.9 vs 13.2; p = 0.638). When stratified by CC16 concentration, there was no difference between mortality in the fluid liberal (36.4 vs 58.8%; p = 0.256) or conservative (4.3 vs 11.8%; p = 0.366) groups. CONCLUSIONS: CC16 demonstrated an acceptable AUROC for prediction of patient mortality with a cut point of 45 ng/mL. Patients with high CC16 on day 1 had worse outcomes compared with those with low CC16, suggesting a prognostic role for this lung-specific biomarker.